Penguatan Kapasitas Caregiver Indonesia dalam Pelayanan Geriatri Internasional melalui Program Cross-Cultural Training - Nur Arifah Astri; Dianis Wulan Sari; Neisya Pratiwindya Sudarsiwi; Woro Mustika Weni; Rizki Fitryasari P.K.; Elida Ulfiana; Santi Martini; Joni Haryanto; Ah. Yusuf S. (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
The growing demand for long-term care in Japan has opened wider opportunities for Indonesian caregivers and nurses to work in geriatric care services. However, working in a cross-cultural care setting requires more than technical caregiving skills. This article aims to explore the experiences of Indonesian caregivers working in older adult’s care facilities in Japan as a basis for identifying preparation needs for future Indonesian caregivers. This article used a qualitative descriptive approach through semi-structured interviews with four Indonesian caregivers who had direct experience in caring for older adults in Japan. The interview data were transcribed and analyzed thematically. The findings identified four main themes: readiness in Japanese language communication and workplace cultural adaptation; understanding of the kaigo role and basic older adults care skills; preparedness in dementia care, ethics, documentation, and patient safety; and mental resilience, social support, and career development. The findings indicate that prospective Indonesian caregivers need realistic preparation before departure, including practical Japanese for geriatric care, understanding of daily caregiving roles, dementia care, ethical awareness, incident reporting, and support from experienced caregivers. These findings can serve as an initial basis for developing cross-cultural geriatric care training for Indonesian caregivers. Keywords: caregiver, cross-cultural care, older adults care, Indonesian workers   ABSTRAK Meningkatnya kebutuhan layanan perawatan jangka panjang di Jepang membuka peluang bagi caregiver dan perawat Indonesia untuk bekerja dalam layanan perawatan lansia. Namun, bekerja dalam konteks geriatri lintas budaya tidak hanya membutuhkan keterampilan merawat, tetapi juga kesiapan bahasa, budaya, etika, dan mental. Artikel ini bertujuan untuk menggali pengalaman caregiver Indonesia yang bekerja dalam layanan perawatan lansia di Jepang sebagai dasar pemetaan kebutuhan persiapan calon caregiver Indonesia. Artikel ini menggunakan pendekatan kualitatif deskriptif melalui wawancara semi-terstruktur dengan empat caregiver Indonesia yang memiliki pengalaman langsung merawat lansia di Jepang. Data wawancara ditranskripsikan dan dianalisis secara tematik. Hasil wawancara menunjukkan empat tema utama, yaitu kesiapan komunikasi bahasa Jepang dan adaptasi budaya kerja; pemahaman peran kaigo dan keterampilan dasar perawatan lansia; kesiapan menghadapi demensia, etika, dokumentasi, dan keselamatan pasien; serta ketahanan mental, dukungan sosial, dan pengembangan karier. Temuan ini menunjukkan bahwa calon caregiver Indonesia membutuhkan pembekalan yang lebih realistis sebelum keberangkatan, terutama terkait bahasa Jepang praktis, gambaran kerja kaigo, perawatan demensia, etika, pelaporan insiden, dan dukungan dari caregiver berpengalaman. Kata kunci: caregiver, Jepang, layanan lansia, perawatan lintas budaya, tenaga kerja Indonesia